Pengembangan pengelolaan perpustakaan di Perpustakaan Politeknik Negeri Bandung - Dimas Saputra (Universitas Pendidikan Indonesia, 2026)
Manual cataloging processes can hinder librarians from performing other tasks. The adoption of technology in cataloging processes can streamline librarians’ work, facilitate information retrieval, and improve access to information. The objective of this initiative is to organize information and technology, including migrating the book security system from conventional methods to Radio Frequency Identification (RFID) technology, as well as streamlining the cataloging workflow, thereby reducing the time required for inputting data on new books—a process previously done manually by hand. Additionally, this initiative helps promote the library to attract more patrons. The stages of this community service project consist of three categories: pre-implementation activities, internship implementation activities, and post-implementation activities. The implementation of the community service project at Unit Penunjang Akademik (UPA) Perpustakaan Polban during the period from November 2025 to January 2026 has produced a number of significant tangible outcomes. One of the most notable achievements in the field of information technology was the initiation of the development of cataloging software. Meanwhile, efforts to bring the library closer to Gen Z student patrons were realized through the production of creative content.